Analysis and tendency of development of interconnected countries of the EEU - Kapysheva, S.K.; Kamenova, M.Zh.; Tursumbaeva, M.Zh. (BUKETOV BUSINESS REVIEW, 2018)
The article examines the state and development trends of the mutual trade of the Eurasian Economic Union countries, as well as the dynamics of the creation of common markets for goods and services. The analysis of mutual trade of the EEU member states for 2015-2016 is given. Are reflected directions, events and decisions that set the vectors of integration processes in the Eurasian Economic Union. Current data and analysis of macroeconomic development, dynamics of mutual trade are given. The volume of intra-union and foreign trade of the EEU member states, the volume of exports and imports from the EEU to third countries, the commodity structure of exports and imports to the EEA, the main directions of exports and imports from the EEU, the commodity structure of intra-union trade, the conditions for foreign trade: the positions of states - the members of the EEU in last years. It is noted that Doing Business 2017, the Republic of Kazakhstan and the Republic of Belarus are counting on the number of countries leading in Central Asia and Europe by reforming the business in the sphere of business regulation. It is worth noting that the Republic of Kazakhstan will be expelled from the sale of foreign contracts, and, in particular, the export operations in the frame of the export operations will result in two documents requiring the removal of the defective goods.